Eckweek, Peasedown St John, Somerset : Survey and Excavations at a Shrunken Medieval Hamlet 1988-90 - Young, Andrew (The Society for Medieval Archaeology Monographs, 2020)
Cover -- Title Page -- Copyright Page -- Table of Contents -- List of Figures -- Acknowledgements -- Summaries (English/French/German/Spanish) -- Abbreviations -- Chapter 1: Introduction -- 1.1: Background to the project -- 1.2: Geology, topography and land use -- Chapter 2: Documentary and Archaeological Background -- 2.1: Documentary, archaeological and landscape evidence (by Dr Nick Corcos, 2013) -- 2.2: The placename Eckweek (by Dr Michael Costen) -- 2.3: Eckweek in Domesday Book (by Dr Frank Thorn) -- Chapter 3: Surveys -- 3.1: Preliminary surveys -- 3.2: Geophysical survey (by Andrew Payne of Historic England, 1989, updated 2015) -- Chapter 4: Excavations -- 4.1: Excavation areas and methodologies -- 4.2: Summary of structural phasing -- 4.3: The excavated evidence -- 4.4: Watching brief -- Chapter 5: Artefacts and Environmental Evidence -- 5.1: Prehistoric ceramics - pottery, briquetage and a bronze-working crucible (by Dr Elaine Morris, 1992, updated 2015) -- 5.2: Romano-British pottery (by Dr Jane Timby, 2015) -- 5.3: The late Saxon, Saxo-Norman, medieval and post-medieval pottery (by Andrew Young and Alexander Kidd, 1990-1991, updated 2015) -- 5.3.1 The petrology of medieval pottery (by D F Williams PhD FSA - Department of Archaeology, University of Southampton, 1991) -- 5.4: Coins (by Sarah Newns, 2015) -- 5.5: Iron and lead objects (by Ann Thompson, 1991) -- 5.6: Copper alloy objects (by Sarah Newns, 2015) -- 5.7: Flint (by Vince Russett, 1991) -- 5.8: Worked stone objects (by Alexander Kidd and Andrew Young, 1991) -- 5.8.1 The petrology of medieval whetstones of sandstone from Eckweek (by Professor Gilbert Kelling - Department of Geology, University of Keele, 1991) -- 5.9: Clay tobacco pipe (by Sarah Newns, 2014) -- 5.10: The composition of a group of later medieval copper alloy 'ingots' and other objects (by Nigel Blades, 1991).